Breast cancer risk in neurofibromatosis type 1 is a function of the type of NF1 gene mutation: a new genotype-phenotype correlation. Issue 4 (10th December 2018) - Frayling, Ian M; Mautner, Victor-Felix; van Minkelen, Rick; Kallionpaa, Roope A; Aktaş, Safiye; Baralle, Diana; Ben-Shachar, Shay; Callaway, Alison; Cox, Harriet; Eccles, Diana M; Ferkal, Salah; LaDuca, Holly; et al.
Abstract : Background: Neurofibromatosis type 1 (NF1) predisposes to breast cancer (BC), but no genotype-phenotype correlations have been described. Methods: Constitutional NF1 mutations in 78 patients with NF1 with BC (NF1-BC) were compared with the NF1 Leiden Open Variation Database (n=3432). Results: No cases were observed with whole or partial gene deletions (HR 0.10; 95% CI 0.006 to 1.63; p=0.014, Fisher's exact test). There were no gross relationships with mutation position. Forty-five (64.3%; HR 6.4–83) of the 70 different mutations were more frequent than expected (p<0.05), while 52 (74.3%; HR 5.3–83) were significant when adjusted for multiple comparisons (adjusted p≤0.125; Benjamini-Hochberg). Higher proportions of both nonsense and missense mutations were also observed (adjusted p=0.254; Benjamini-Hochberg). Ten of the 11 missense cases with known age of BC occurred at <50 years (p=0.041). Eighteen cases had BRCA1/2 testing, revealing one BRCA2 mutation. Discussion: These data strongly support the hypothesis that certain constitutional mutation types, and indeed certain specific variants in NF1 confer different risks of BC. The lack of large deletions and excess of nonsenses and missenses is consistent with gain of function mutations conferring risk of BC, and also that neurofibromin may function as a dimer. The observation that somatic NF1 amplification can occur independently of ERBB2 amplification in sporadic BC supports this concept. A prospective clinical-molecular study of NF1-BC needs to be established to confirm and build on these findings, but regardless of NF1 mutation status patients with NF1-BC warrant testing of other BC-predisposing genes.